Analysis of Heat and Mass Transfer of Fractionalized MHD Second-Grade Fluid over Nonlinearly Moving Porous Plate. (23rd May 2022) - Jamil, Muhammad; Ahmed, Israr; Khan, Ilyas; Faryaz, Umar; Alghtani, Abdulaziz H.; Andualem, Mulugeta
Abstract : This study investigates the heat and mass transfer in the MHD flow of fractionalized second-grade fluid induced by impulsively moved bottom porous plate with nonlinear velocity of the magnitude KTD. To acquire the fractionalized nondimensional set of flow administering differential equations, fractional calculus and dimensionless variables are considered. The solution process utilizes Laplace transform and results in the acquired outputs in terms of generalized functions. The exact solutions for concentration, temperature, velocity, and the shear stress are then reduced by certain limits into fractional/traditional second-grade and Newtonian fluids as per the special cases within and out of the magnetic and porous effects. It is observed that these special cases occur in the previous published literature which verify the results of this study. The results are pictorially visualized to perform the analysis for impacts of diverse physical parameters and dimensionless quantities on concentration, temperature, and velocity fields. It is learned from the analysis that magnitude of viscoelastic parameter is directly proportional to velocity whereas the porous and magmatic effects are inversely proportional. Increasing fractional parameter values reduce flow fields of velocity and temperature. Effects of dimensionless parameters for heat and mass transfer are analysed in detail.